Liberty and democracy - Machan, Tibor R. (Philosophic reflections on a free society., 2002)
In Liberty and Democracy, contributors grapple with the issue of the proper role of democracy in a society that is committed to respecting protecting the individual rights of all. They challenge conventional thinking, offering provocative ideas on democracy and individual freedom.